Novel Poly(ionic liquid) Augmented Membranes for Unconventional Aqueous Phase Applications in Fractionation of Dyes and Sugar - DePaz, Sandrina (Polymers (Basel), 2021)
Poly(ionic) liquid (PIL) augmented membranes were fabricated through self-polymerization of 2-vinyl pyridine and 4-vinyl pyridine followed by dopamine triggered polymerization and bridging with inert polyamide support. The resulting membranes acquired a positive surface charge with a high degree of hydrophilicity. Fourier transformed Infra-red (FTIR) and Energy dispersive X-ray (EDX) spectroscopic investigation revealed the successful augmentation of PIL surface layer, whereas surface morphology was investigated through scanning electron microscopy (SEM) imaging. This manuscript demonstrates pi electron-induced separation of dyes with the trend in permeability: Coomassie Brilliant Blue G (CBBHG) > Remazol Brilliant Blue R (RBBR) > Eichrome Black T (EBT) > Congo Red (CR). CBBG exhibited extended conjugation over large aromatic domain. RBBR and EBT were associated withtheelectron-donating -NH(2) group and electron-withdrawing -NO(2) group, respectively, hence pi electron density on aromatic ring varied. The steric repulsion between two pairs of ortho hydrogens (Hs) in biphenyl moieties of CR resulted in deviation of planarity and hence aromaticity leading to the lowest permeability. The sugar fractionation followed the trend: Galactose > Mannose > Fructose > Glucose > Xylose. More hydroxyl (-OH) groups in sugars and their conformational alignment in the same direction, exhibited more lone pair of electrons leading to more interaction with PIL and hence better permeability. Pentose showed poorer permeation than hexose, whereas aldose showed better permeation than ketose.